ASTEROID POSITIONS BASED ON THE DUSHANBE PART OF THE FON PROJECT OBSERVATIONS - Shatokhina, S V.; Relke, H.; Mullo-Abdolov, A. Sh; Yizhakevych, O. M.; Yuldoshev, Q. X.; Protsyuk, Yu. I.; Andruk, V. M. (Одеські астрономічні публікації, 2020)
Asteroid images identification and crea- tion the positional catalogs based on digitized photograph- ic observations of previous years were continued. Namely, the cooperation between Ukrainian Virtual Observatory (UkrVO) and the Institute of Astrophysics of the Academy of Sciences of Tajikistan make it possible to expand this work by involving numerous additional archives of digitized observations and processing services and thus obtaining new original data about the Universe. The Dushanbe part of the Northern Sky Survey (FON project) is represented by about 1570 photographic plates obtained in 1985-1992 on the Zeiss-400 astrograph at the Hissar Astronomical Observatory of the Institute of As- trophysics of the Academy of Sciences of Tajikistan. At present, their digitization and further scan processing con- tinue until the final product is obtained in the form of a catalog of equatorial coordinates and stellar magnitudes for all registered objects on the plates. The equatorial co- ordinates α, δ of all objects on the plates were obtained in the Tycho-2 reference system at the epoch of exposure of each plate. Photometry of stars for the plates was carried out based on the principles implemented in the processing of the plates of the FON project using photoelectric meas- urements of stars to construct the characteristic curves of the plates. Photographic B-magnitudes of objects were calibrated with photoelectric standards. In parallel with solving the main task of the project to cre- ate a catalog of stars and galaxies, we analyzed the results of processing the plates to search for images of asteroids and comets and create a catalog of their coordinates and values. About 300 positions of asteroids and comets were obtained with visual magnitudes from 7 to 16.5. All positions of the asteroids were compared with the ephemeris. A preliminary analysis of the O-C differences and their comparison with similar results obtained from the digitized observations of the Kyiv and Kitab parts of the FON project are conducted.